2015
DOI: 10.1158/1541-7786.mcr-15-0240
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiredoxin Promotes Colorectal Cancer Cell Invasion and Metastasis through a Novel Mechanism of Enhancing EGFR Signaling

Abstract: Sulfiredoxin (SRXN1/Srx) is a multifunction enzyme with a primary antioxidant role of reducing the overoxidized inactive form of peroxiredoxins (Prxs). The function and mechanisms of Srx in cancer development are not well understood. Here, Srx is preferentially expressed in human colorectal cancer (CRC) cells but not in normal colon epithelial cells. Loss-of-function studies demonstrate that knockdown of Srx in poorly differentiated CRC cells not only leads to the inhibition of colony formation and cell invasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…shRNAs of EGFR, MMP-1, and HIF-1␣ were from Origene (Rockville, MD). p3XFLAG-CMV/EGFR and its control plasmids were kindly provided by Dr. Qiou Wei (Department of Toxicology and Cancer Biology, University of Kentucky) (58). Bradford protein assay reagent was from Bio-Rad.…”
Section: Discussionmentioning
confidence: 99%
“…shRNAs of EGFR, MMP-1, and HIF-1␣ were from Origene (Rockville, MD). p3XFLAG-CMV/EGFR and its control plasmids were kindly provided by Dr. Qiou Wei (Department of Toxicology and Cancer Biology, University of Kentucky) (58). Bradford protein assay reagent was from Bio-Rad.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of redox homeostasis, resulting in elevated levels of reactive oxygen species in tumor cells has been implicated in the promotion of tumor progression and development of drug resistance . Genes upregulated in LoY compared with non‐LoY cases included members of the AKRs superfamily of NAD(P)H‐linked oxidoreductases, such as AKR1B10, AKR1C1, AKR1C2, AKR1C3, as well as ALDH3A1, G6PD, GPX2, PIR, SRXN1, and TXNRD1, which are increasingly recognized for their important roles in drug detoxification and xenobiotic metabolism . In particular, the upregulation of AKR1C1, AKR1C2, and G6PD are all associated with resistance to cisplatin‐based chemotherapy in lung cancer, whereas upregulation of AKR1C3 is linked to insensitivity to radiotherapy in oesophageal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…34 Genes upregulated in LoY compared with non-LoY cases included members of the AKRs superfamily of NAD(P)H-linked oxidoreductases, such as AKR1B10, AKR1C1, AKR1C2, AKR1C3, as well as ALDH3A1, G6PD, GPX2, PIR, SRXN1, and TXNRD1, which are increasingly recognized for their important roles in drug detoxification and xenobiotic metabolism. [24][25][26][35][36][37][38][39][40][41][42] In particular, the upregulation of AKR1C1, AKR1C2, and G6PD are all associated with resistance to cisplatin-based chemotherapy in lung cancer, 24,26 whereas upregulation of AKR1C3 is linked to insensitivity to radiotherapy in oesophageal cancer. 25 In a recent study of head and neck cancer, tumor redox was associated with poorer patient outcomes, suggesting that its measurement, for example, by 62Cu-ATSM PET, could be a useful prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that K721 and K846 residues of EGFR are important for maintaining EGFR kinase activity, whereas, K1037 and K1164 are important sites of acetylation required for receptor internalization (30). In another study, Jiang et al reported that inhibition of K1037 acetylation by an oncogenic protein, Sulfiredoxin (Srx), can promote sustained EGFR activation (37). Taken together, we hypothesize that SMURF2-UBCH5-mediated ubiquitination at K721 and K846 residues may be critical in constitutive activation of the mutant EGFR, whereas, ubiquitination at K1037 and 1164 may be competing with acetylation to balance receptor internalization, membrane retention, and protein stability.…”
Section: Discussionmentioning
confidence: 99%